DETERMINAN KECURANGAN AKADEMIK PADA PEMBELAJARAN HYBRID - Sarwenda Biduri; Adelia Asma; Santi Rahma Dewi; Nurasik Nurasik (STIE Mahardhika, 2023)
Academic cheating is a growing problem in hybrid education. There is research that focuses on the causes of academic cheating, but the research results are conflicting. The purpose of this study is to find the consistency of the factors that influence academic fraud, especially the fraud triangle. This research method uses a quantitative approach. Partial t test data analysis technique for testing hypotheses on IBM SPSS version 26 software. The research subjects were accounting students at Muhammadiyah University of Sidoarjo class of 2018, totaling 73 respondents. A simple random sampling technique was used to determine the research sample and the number of samples was determined using the Slovin formula. This study shows that the influential and unaffected variables, namely the opportunity and rationalization variables, have an effect on academic cheating in hybrid learning. While the variables Pressure and Gender have no effect on academic cheating during hybrid learning